ACARA MY TRIP MY ADVENTURE DAN PERILAKU PENONTON (Pengaruh Acara My Trip My Adventure di Trans TV terhadap Perilaku Penonton dikalangan Karang Taruna Desa Jatirejo Kecamatan Jumapolo Kabupaten Karanganyar) - Nurnawati, Retno Safitri, Bedjo Sukarno & (Transformasi, 2016)
In this research method used is the method of survey eksplanatif that is associativewith research the relationship (correlation). Research location in the village of Jatirejo,district Jumapolo, Karanganyar Regency. The samples used in this study are teenagers aged 15-19 years as many as 38 people with random sampling, analysis techniques areused namely nalisis Kendall's tau correlation.. With the results of koefisisen correlation of 0.551and known values of count and ï´.table, namely 0.551 > 0.025. Because t.count greater than t.table, then look that there was significant influence between the "Event of My Trip My Adventureagainst behavior on an audience with significant levels adequate for the 5% (0.05) trust, then thebehavior on coral midshipman Jatirejo Village, Jumapolo Sub-district, Karanganyar Regency isaffected by the events of My Trip My Adventure in Trans TV and the rest in influence by othervariables.Keywords: Event My Trip My Adventure, watching television, behavior